Produção de proteína recombinante a de superfície de pneumococo em escherichia coli: análise econômica e influência da plataforma de expressão - Cardoso, Valdemir Moretto (2019)
Streptococcus pneumoniae diseases represent a widespread public health. Pneumococcal surface protein A (PspA), which is recognized as one of the main virulence factors of this bacterium, has gained relevance in coverage and protection when used as part of conjugated vaccines or antigenic subunits. To a large scale offer, PspA may be produced by Gram-negative bacteria genetically modified as Escherichia coli. Nevertheless, E. coli strains, which are commonly used as expression platforms of recombinant proteins, produce lipopolysaccharides (LPS), an endotoxin that can cause adverse reactions whether it is present in vaccine compositions. This fact may demand additional steps during protein purification and contribute to increase process cost of this vaccine production. In 2013, a new E. coli BL21(DE3) strain (ClearColi®) has been commercially available. This strain synthesizes a genetically modified LPS, which is endotoxin-free. However, PspA production in such organisms has not been assessed yet and the impact of different strategies of cultivation and economical process implications are not known. Then, the present work had as objective to evaluate PspA4Pro process production using ClearColi® and conventional E. coli BL21(DE3) cells harboring the plasmid pET37b(+)/pspA4Pro as expression platforms to PspA4Pro, an untagged fragment of PspA with immunogenic potential. The best conditions of temperature, induction and complex medium composition evidenced in shaker flasks were evaluated in bioreactor during batch and fed-batch modes in order to intensify PspA4Pro production. Bioreactor cultivations using defined medium were performed for comparisons. Studies involving conventional E. coli BL21(DE3) focused mainly on evaluating an ordinary extract from soy supplement for human consumption as alternative nitrogen source in shaker and bioreactor (31 °C, autoinduction with lactose) assays. In order to assess the impact of different process conditions on component, energy and gases expenses, it was developed and applied an economic analysis from 9 bioreactors cultivations using conventional E. coli (in which were compared defined and complex media, lactose and IPTG as inducers and temperatures from 27 to 37 °C) and cultivations using ClearColi® (five) in different media, IPTG concentrations and operation modes (batch and fed-batch). Into the studied conditions, the economic results demonstrated that PspA4Pro production in simple batches may be more cost-effective than fed-batches, despite the latter have presented higher recombinant protein titers and productivities. Economic results based on conventional cell experiments showed that using IPTG as inducer in a higher scale was more viable, while lower costs were obtained in cultivations at 32 °C using defined medium, even though peptone (or alternative nitrogen sources) prices below US$ 30.00/kg turn the complex medium the best choice. Although PspA-biomass bioreactor yield using ClearColi® (173±21 mgPspA/gDCM at 32 °C with complex medium and induced by IPTG 0.70 mM) was the same order of the best values as conventional cultivations, the ClearColi® protein direct costs were the highest ones under similar production strategies. Endotoxin-free E. coli strain is scalable and promising as an expression platform of recombinant proteins.